2006
DOI: 10.1007/s00264-006-0158-z
|View full text |Cite
|
Sign up to set email alerts
|

Histoacryl glue in meniscal repairs (a biomechanical study)

Abstract: The purpose of this study was to investigate the biomechanical efficacy of Histoacryl (cyanoacrylate, Nasetil 2 butyl sistein) in meniscal tear repair. In our study, the primary stability of three different repair techniques in delaying the formation of a gap of 2 mm was investigated. A meniscal tear was repaired with two vertical sutures and Histoacryl in the first group; it was repaired only with Histoacryl in the second group, and with only two vertical sutures in the third group. Menisci were then placed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…These have been used in thoracic aortic repair,196, 199 abdominal surgery,192 corneal perforations,194 nerve,198 lung,197 plastic surgery193, 195, 200 and otology 201. Most recently they have also been applied in tension and weight‐bearing connective tissues such as the meniscus to reattach bucket handle tears202, 203 and in the fixation of talar osteochondral fractures 204. Two biological glues based on an adhesive protein extracted from the marine mussel Mytilus edulis 205, 206 and a protein‐based adhesive elastomer secreted by the Australian frog Notaden bennetti 207, 208 have also recently been developed, which have superior adhesive properties to conventional fibrin glues.…”
Section: Integration Of Bioscaffold Constructs Into Cartilaginous Defmentioning
confidence: 99%
“…These have been used in thoracic aortic repair,196, 199 abdominal surgery,192 corneal perforations,194 nerve,198 lung,197 plastic surgery193, 195, 200 and otology 201. Most recently they have also been applied in tension and weight‐bearing connective tissues such as the meniscus to reattach bucket handle tears202, 203 and in the fixation of talar osteochondral fractures 204. Two biological glues based on an adhesive protein extracted from the marine mussel Mytilus edulis 205, 206 and a protein‐based adhesive elastomer secreted by the Australian frog Notaden bennetti 207, 208 have also recently been developed, which have superior adhesive properties to conventional fibrin glues.…”
Section: Integration Of Bioscaffold Constructs Into Cartilaginous Defmentioning
confidence: 99%
“…In medical practice, n-butyl-and octyl-cyanoacrylate are most commonly used. Both biomechanical [94,95] and cytotoxic [96][97][98] properties of cyanoacrylate have been tested extensively. n-Butyl-2-cyanoacrylate have been approved for internal use including atriovenous embolization [99], endoscopic treatment of bleeding ulcers [100,101], occlusion of biliary [102] and pancreatic fistulas [103], fixation of polypropylene mesh in open [104,105] and laparoscopic hernia repair [106].…”
Section: Cyanoacrylatementioning
confidence: 99%
“…In orthopedic literature, cyanoacrylate (Dermabond ® ) has been used for skin closure with excellent result when compared with staples after total joint arthroplasty. A biomechanical study on the use of cyanoacrylate (Histoacryl ® ) for meniscal repair, reported decrease failure rates when compared to vertical suture repair [95] but no in vivo study is yet available. Octyl-cyanoacrylate was used to fix meniscal transplant in a rabbit model, the authors had to sacrifice all animals earlier than planned due to severe inflammatory reaction with caseous necrosis in the operated joint and they have recommended against the use of octyl-cyanoacrylate to fix transplanted menisci [107].…”
Section: Cyanoacrylatementioning
confidence: 99%
“…Octyl-cyanoacrylate cyanoacrylate, N-asetil 2 butyl sistein and fibrin are the most commonly used materials [5,55]. The orthopaedic uses include meniscal repairs and repairs of the annularus fibrosis [55,104].…”
Section: Tissue Gluementioning
confidence: 99%
“…The orthopaedic uses include meniscal repairs and repairs of the annularus fibrosis [55,104]. Both of these applications require more strength than can be achieved by tissue glue alone but in combination with sutures tissue glue improves the contact between the apposed edges and for limited posterior horn applications might be sufficient without sutures [5,64,87]. Fibrin glue appears to be adequate to contain cell (chondrocyte) implantations.…”
Section: Tissue Gluementioning
confidence: 99%